PENGARUH VARIASI KOMPOSISI BRIKET ORGANIK TERHADAP TEMPERATUR DAN WAKTU PEMBAKARAN - Tarsito, Teguh; Sutanto, Heri; Marhaendrajaya, Indras (BERKALA FISIKA, 2013)
It has been carried out to study of influence of variation composition in organic briquetteabout temperature and duration time combustion briquette that was optimum. Briquette had made that was  briquette with composition rice hull, briquette with composition rice hull and sawdust wood rubber that mixed with glue from amylum gel. Experimental method was used in this research. Briquette sample  was burned and measured the temperature of combustion so we gained the values between temperature with combustion briquette duration time of sample briquette,briquette mass before combustion and mass residue of combustion. From the result of this researchthe conclusions can be made were the sample briquette   have  highest temperature of combustionand longest  duration time of  combustion was sample briquette with composition rice hull andwood rubber sawdust = 4 grams : 6 grams with oven  temperatur  100oC because have longestduration time combustion  over temperature  100oC with fluctuation 100°C-150°C was 12 minutes.Keywords :  briquette,  combustion calor, rice hull